Bedside dysphagia screens in patients with traumatic cervical injuries: An ideal tool for an under-recognized problem. Issue 4 (October 2018) - Posillico, Sarah E.; Golob, Joseph F.; Rinker, Andrea D.; Kreiner, Laura A.; West, Rebecca S.; Conrad-Schnetz, Kristen J.; Kelly, Michael L.; Claridge, Jeffrey A.
Abstract : BACKGROUND: We initiated a prospective interventional study using a nurse-driven bedside dysphagia screen (BDS) in patients with cervical spine injury (CI) to address three objectives: (1) determine the incidence of dysphagia, (2) determine the utility of the new BDS as a screening tool, and (3) compare patient outcomes, specifically dysphagia-related complications, in the study period with a retrospective cohort. METHODS: All patients with CI admitted to a Level I trauma center were enrolled in a prospective 12-month study (June 2016–June 2017) and then were compared with a previous 18-month cohort of similar patients. Our new protocol mandated that every patient underwent a BDS before oral intake. If the patient failed the BDS, a modified barium swallow (MBS) was obtained. Exclusion criteria were emergency department discharge, inability to participate in a BDS, leaving against medical advice, BDS protocol violations, or death before BDS. A failed MBS was defined as a change in diet and a need for a repeat MBS. Dysphagia was defined as a failed MBS or the presence of a dysphagia-related complication. RESULTS: Of 221 consecutive prospective patients identified, 114 met inclusion criteria. The incidence of dysphagia was 16.7% in all prospective study patients, 14.9% in patients with isolated CI, and 30.8% in patients with spinal cord injury. The BDS demonstrated 84.2% sensitivity, 95.8% specificity, 80.0% positive predictive value, and 96.8% negative predictive value. There were no dysphagia-related complications. The prospective study patients demonstrated significantly less dysphagia-related complications ( p = 0.048) when compared with the retrospective cohort of 276 patients. CONCLUSIONS: The introduction of the BDS resulted in increased dysphagia diagnoses, with a significant reduction in dysphagia-related complications. We recommend incorporating BDS into care pathways for patients with CI. LEVEL OF EVIDENCE: Study type diagnostic test, level III.